Teknologi dan Manusia : Tinjauan Dalam Perspektif Filsafat Etika - Nur Insani, Galuh; Salwa Cantika Khoirunnisa; Yusuf Tri Herlambang (PT. ALHAFI BERKAH INDONESIA, 2023)
This article explores the close relationship between philosophy and science as ethical guides in the development and application of technology. Philosophy provides a framework of values of Human Rights (HAM), justice, freedom and responsibility that are important to ensure technology is used in a beneficial and safe manner for humans and the environment. This research is qualitative research in the nature of a literature study or literature review. The literature review method is a method carried out by collecting and reading existing sources of information. The findings of this article include the urgency of considering the social, cultural and sustainability impacts of technology, as well as promoting sustainable and responsible innovation. Philosophy as an ethical guide is shown to be the key to bridging the complexity of the relationship between technology and humans.